PRINSIP-PRINSIP METODE PENDIDIKAN ISLAM DALAM ALQURAN - Fadriati Fadriati (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2012)
In the first revelation, Allah has commanded man kind to read, to learn and to teach by means of media. By education, man has knowledge. Therefore, education must be carried out by means of effective methods to arrive at the expected goals. In thematic analysis, the Holy Quran in an-Nahl verse 125 points out three general principle method in Islamic teaching: al-hikmah, al-mau’izah al-hasanah and al-mujadalah. The Quran has demanded that education should be carried out on the basis of wisdom, humanism, and pluralism and full of tenderness and love.Kata kunci: metode pendidikan Islam, al hikmah, al mau’izhah al hasanah, al mujadalah